Frontier Finance - Microfinance as a Prudent First Intervention in Post-Conflict Countries - Earne, Julie; Gutin, John; Jagun, Jumoke (World Bank, Washington, DC, 2012)
While there is growing support for microfinance globally, the unmet demand remains enormous, particularly in Africa, and especially in post-conflict and frontier countries. In Liberia, Sierra Leone, the Central African Republic and the Democratic Republic of Congo (DRC), less than 1 percent of the population has access to a bank account. Yet as these countries continue to stabilize, the demand for secure financial services is exploding. The post-conflict nature of these countries magnifies the need for microfinance services, as micro and small enterprises (MSEs) operating at a subsistence level are often the only surviving businesses after a conflict.